KITAB FIKIH ULAMA BANJAR Kesinambungan Dan Perubahan Kajian Konsep Fikih Lingkungan - Sukarni, Sukarni (Analisis: Jurnal Studi Keislaman, 2015)
FIQH TEXTS BANJARESE ULAMA CONTNUITY AND DEVELOPMENT STUDY OF FIQH ECOLOGY: Fiqh texts play an important role in the Muslim community throughout the ages. Fiqh texts become the code of conduct for Muslim to make their deeds valid and in accordance with the teachings  of Islam. Fiqh texts as intellectual  products have an important role to determine the level of creation and as means to observe the progress of the intellect of a Muslim community. In addition, fiqh texts produced can  be  a  hint  towards  a  particular  school  of  thought  and  as critical study materials to perform continuity and development of intellectual  work. Banjarese Ulama (from Banjarese ethnic)  are known by their religiosity. The work in the field of jurisprudence was  also  born from  them  since  Sabilal  Muhtadin  in  the  18th century  until Mabadi Ilmu ‘Fiqh of the 20th century.  However, the continuity  of the  intellectual work that  appreciates  for the environment, especially on water ecology, which characterizes the ecology of Banjar, is inadequate. This shows the “unthinkable” in an intellectual  creation, as described in the results of this study.